The determinants of foreign direct investments: Regional vs. National characteristics - Laura Resmini; Laura Casi (European Regional Science Association (ERSA), 2010)
This study aims at identifying the main determinants of Foreign Direct Investment (FDI) into the European regions. The theory of the determinants of FDI deals with the question on why firms become multinationals. Partial equilibrium studies suggest that in so doing firms try to internalize trade costs and externalities from firms specific assets as well as to take advantages from location characteristics. General equilibrium models turn the attention to motivations for investing abroad, distinguishing between market seeking and efficiency seeking FDI. While the former are more interested in local markets, the latter are looking for lower-cost inputs and strategic assets that help them to become not only more efficient but also more competitive. According to this theoretical background, the most important determinants of FDI are market size and potential, factor costs, agglomeration externalities, labour skills, trade barriers and incentives. However, the empirical literature is mainly based on evidence drawn from data at industry or country level. Therefore, we need to investigate whether and to what extent those variables maintain their capacity of attraction at regional level, too. At this purpose, we argue that, at regional level, the capacity to attract FDI is the result, on the one hand, of the relative performance of a region within the country it belongs to, and, on the other hand, of the relative performance of the country it belongs to in Europe. In order to achieve our research objectives, we use original data on the number of foreign investments over the 2005-07 period disaggregated by regions of the EU27 and by sectors. Our empirical analysis is divided into two interrelated parts. We first perform a detailed analysis of the location determinants of foreign investments at both regional and country level. Then, we try to understand whether and what extent each region's capacity to attract FDI is enhanced or hampered by the performance of the country it belongs to by interacted regional and country variables. Once identified the "national" and the "regional" components of factors able to attract FDI, more effective FDI promotion policies can be implemented at national, regional and sectoral levels.
Keywords: 330; Foreign direct investments; globalization